The Effect of Fishery Management on the Yield of the Critically Endangered European Eel Anguilla anguilla in Mesotrophic Rivers and Streams in Central Europe - Roman Lyach (Fishes, 2022)
The European eel Anguilla anguilla is a critically endangered catadromous migratory fish species. To conserve eel populations, angling restrictions and stocking activities are often used. This paper aimed to analyze the effect of an increased minimum legal angling size, eel stocking, fishing effort, and important environmental and biological factors on eel yield. This study used data on eel stocking and yield collected by the Czech Fishing Union using angling logbooks. Data regarding 41 tons of harvested eels were collected on 176 fishing sites from 38,000 anglers over the years 2005–2018 in central Bohemia and Prague (the Czech Republic). Eel made up only 0.006% of the overall fish harvest by biomass. It was found that the increased minimum legal angling size led to decreased yield of eel and to a decreased percentage of eel in the overall fish harvested. It also led to larger harvested eels, while the number of fishing sites where anglers harvested eels stayed constant over time. The eel yield was strongly correlated to the angling effort but not to the eel stocking intensity or the environmental and biological factors. In conclusion, implementing the minimum legal angling size did achieve its goal, because it led to decreased eel yield.